Every body on deck - McKevett, G. A. (McKevett, G. A. Savannah Reid mystery., 2017)
When famed mystery writer Natasha Van Cleef invites the Moonlight Magnolia Detective Agency on an Alaskan cruise in exchange for some personal protection, Savannah is instantly onboard with the idea. The voyage goes smoothly<U+2014>until Natasha and her husband flee the ship and get killed in a suspiciously explosive crash . . . Awash in regret, Savannah and the MM crew won<U+2019>t return home to San Carmelita until they expose whoever caused the fatal “accident.” But Savannah and her team discover that Natasha<U+2019>s life was far more dramatic than any of her bestsellers. Not only was her marriage and literary career splattered with bad blood, but a crazed fan was tracking her every move. With suspects and clues flooding in by the boatful, it<U+2019>s all hands on deck as Savannah rushes to seize the murderer before she lands herself in hot water next . . .